(untitled) (Al-Qamar, 2024)
The study discovers social outline within Sufism (Saintism) instrumentalized by Sufis (saints) to settle peace in the formerly feudal Indo-Pak subcontinent. This research discovered that Sufi’s doctrine, methodology and approach is significant, essential, and valuable to put an end to aggression, extremism, and terrorism that humanity faces now. Sufism as a magical movement attempted for the self-development of human being by following zealously the conducts and fictional character of Prophet Muhammad to achieve supreme surmounting to God. In Subcontinent (Indo-Pak), Sufism as an organization developed parallel to the expansion of Delhi Sultanate (reign of Delhi Sultnas, the kings), in 11th and 12th centuries as a mystical, rational, and communal authority aimed to build and strengthen connections among numerous communities for advancement of spirituality, social justice, human growth and multiplicity. Sufis from various academic regulations adopted different approaches to keep relations with rulers. Sufi movements stressed on the self-determination, self-respect, universality of humanity, fairness, peace, and harmony as vital promoting factors for the development of the planet. Sufi saints typically instrumentalized human growth through spiritual exercise formally besides informal schooling for promotion of peace, harmony, interfaith discourse through their mediatory role in consistent with Maslow’s grading of needs as circulated by Davis Chowning, and well-established communication tactic as enunciated by critical philosophers. Regardless of several opposing groups within, Sufism continued, and the practice is still relevant for managing the contemporary-day challenges comprising extremism, prejudice, and terrorism. In modern-day World, though there are some mystical movements but there is need to reinforce these movements with the help of modern state approach to have consistent peace and development of society at substantial.